Ответы и объяснения

Лучший Ответ!
2013-05-13T23:22:45+00:00

\left \{ {{x-y=1} \atop {x^2-y=3}} \right.\\\left \{ {{y=x-1} \atop {x^2-(x-1)=3}} \right\\\left \{ {{y=x-1} \atop {x^2-x+1-3=0}} \right.\\\left \{ {{y=x-1} \atop {x^2-x-2=0}} \right. 

Решу уравнение отдельно:

x^2-x-2=0\\D=1+8=9\\\sqrt{D}=3\\x_{1}=\frac{1+3}{2}=2\ \ \ \ \ \ \ x_{2}=\frac{1-3}{2}=-1

x1=2                               x2=-1

y1=2-1=1                       y=-1-1=-2

2)\frac{6^{-4}*6^{-9}}{6^{-12}}=6^{-4}*6^{-9}*6^{12}=6^{-4+(-9)+12}=6^{-1}=\frac{1}{6}

2013-05-13T23:25:30+00:00

1. х=1+y            x=1+y      x=2 x=-1

    1+2y+y²-y=3 y²+y-2=0 y=1 y=-2

Ответ:(2;1) (-1;-2)

 

2.6^(-4-9+12)=6^(-1)=1/6

 

Выбираем лучшее решение!